2011
DOI: 10.1093/jxb/err136
|View full text |Cite
|
Sign up to set email alerts
|

The OsNRAMP1 iron transporter is involved in Cd accumulation in rice

Abstract: Cadmium (Cd) is a heavy metal toxic to humans and the accumulation of Cd in the rice grain is a major agricultural problem, particularly in Asia. The role of the iron transporter OsNRAMP1 in Cd uptake and transport in rice was investigated here. An OsNRAMP1:GFP fusion protein was localized to the plasma membrane in onion epidermal cells. The growth of yeast expressing OsNRAMP1 was impaired in the presence of Cd compared with yeast transformed with an empty vector. Moreover, the Cd content of OsNRAMP1-expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
347
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 496 publications
(362 citation statements)
references
References 46 publications
12
347
3
Order By: Relevance
“…3), suggesting that ZIP1 may play crucial roles in the early absorption of Cd. NRAMP1 can be considered a kind of Fe transporter in plants, and its expression can be induced by Fe deficiency in roots [19]. Cailliatte et al [18] demonstrated that the metal transporter NRAMP1 was high-affinity Mn uptake that is essential for growth in conditions of low Mn availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), suggesting that ZIP1 may play crucial roles in the early absorption of Cd. NRAMP1 can be considered a kind of Fe transporter in plants, and its expression can be induced by Fe deficiency in roots [19]. Cailliatte et al [18] demonstrated that the metal transporter NRAMP1 was high-affinity Mn uptake that is essential for growth in conditions of low Mn availability.…”
Section: Discussionmentioning
confidence: 99%
“…NRAMP1 is localized in the plasma membrane of root cells, functioning as a high-affinity transporter for Mn uptake [17]. AtNRAMP1 expression induced by Fe deficiency in roots is thought to control Fe homeostasis in plants [18][19] and may be involved in an enhanced influx of Cd into the cells, causing Cd toxicity [20][21]. HMA3 may be involved in the detoxification of metals by chelating Cd into the vacuole [22].…”
mentioning
confidence: 99%
“…The difference between the models of common plants and Cd-hyperaccumulators laid in the different effects of OsNramp1 and OsNramp5 on Cd accumulation. For instance, OsNramp1 localized in the plasma membrane and the level of OsNramp1 expression was higher in high-Cd-accumulating indica cultivars such as Habataki than in low-Cd-accumulating japonica cultivars such as Sasanishiki [6]. The reflection of these in the models was that the effect of OsNramp1 on Cd that existing in a free state are different.…”
Section: Modelsmentioning
confidence: 96%
“…OsNramp1 expression was observed mainly in roots and was higher in the roots of a high-Cdaccumulating cultivar than in those of a low-Cd-accumulating cultivar [1]. OsNramp5 was mainly expressed in the roots and localized in the plasma membrane of exodermis and endodermis cells of the roots [2].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation